DIGITAL MARKETING STRATEGY OF FEDIA CREATIVE SOCIAL MEDIA AGENCY IN MANAGING BRAND REPUTATION - M. Diaz Satria; Abdul Rasyid (Program Pascasarjana UIN Sumatera Utara, 2026)
In the era of digital disruption, brand reputation has become a highly fragile intangible asset, susceptible to negative sentiments. This phenomenon demands a transformation in the role of social media agencies, shifting from mere content promoters to guardians of corporate image. This study aims to analyze the digital marketing strategies implemented by Fedia Creative, a social media agency, in managing and maintaining client brand reputation. The study employs a qualitative approach with a case study design. Data collection was conducted through participatory observation and in-depth interviews with key informants selected via purposive sampling, including the Head of Digital Marketing, Social Media Specialist, and Content Creator. Data analysis follows the interactive model by Miles, Huberman, and Saldaña. The primary focus of this research highlights the agency's functional shift from offensive strategies (brand awareness) to defensive strategies (reputation guarding). The findings are expected to delineate Fedia Creative's working mechanisms, ranging from strategic content planning and audience interaction management to Standard Operating Procedures (SOP) for crisis communication mitigation. This research provides a theoretical contribution regarding an agency-based reputation management model that is adaptive to the dynamics of algorithms and digital audience psychology.